2022
DOI: 10.1177/09603271221119178
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolomics study of vancomycin-associated nephrotoxicity based on ultra-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry

Abstract: Drug-induced nephrotoxicity is widespread and seriously affects human health. Vancomycin is a classical glycopeptide antibiotic. Vancomycin is widely used for severe infections caused by Gram-positive bacteria, especially methicillin-resistant Staphylococcus aureus but its obvious nephrotoxicity affects the safety of its clinical application. However, the etiology of vancomycin induced kidney injury is not well understood. This study aimed to explore the potential mechanism of vancomycin-induced nephrotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Early identification of AKI in patients receiving vancomycin could enable clinicians to stop or change therapy before irreversible toxicity results. In a study exploring the potential mechanism of VIKI in rats, the authors performed urinary metabolomic analysis on animals treated with intraperitoneal vancomycin for 2, 4, 7 days, and control (saline) [50]. They reported that amino acid metabolism and energy metabolism were disturbed in rats with vancomycin-associated nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification of AKI in patients receiving vancomycin could enable clinicians to stop or change therapy before irreversible toxicity results. In a study exploring the potential mechanism of VIKI in rats, the authors performed urinary metabolomic analysis on animals treated with intraperitoneal vancomycin for 2, 4, 7 days, and control (saline) [50]. They reported that amino acid metabolism and energy metabolism were disturbed in rats with vancomycin-associated nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%